The Role of Islamic Social Finance in Muslim Countries: R-Biblioshiny Application - Zhulal; Aswad, Muhammad (SMART Insight, 2024)
This bibliometric study discusses the current condition of documents about Islamic social finance documents published in journals equipped with digital object identifiers registered in the Scopus database. The analysis is focused on describing the characteristics and trends of keywords, authors and journals. Data analyzed from 59 research publications on scopus. The search keyword is